Obstetric triage systems: a systematic review of measurement properties (Clinimetric) - Asieh Moudi; Mina Iravani; Mahin Najafian; Armin Zareiyan; Arash Forouzan; Mojgan Mirghafourvand (BMC Pregnancy and Childbirth, 2020)
Abstract Background Since labor and delivery units often serve as emergency units for pregnant women, the use of obstetric triage systems with poor or inadequate quality can lead to unintended consequences such as over and under-triage and so a waste of humans and financial resources. Therefore, this systematic review was conducted to evaluate the measurement properties of obstetric triage tools. Methods PubMed, EMBASE, and Medline were searched to identify studies in October 2018 and were updated in May 2019. The risk of bias COSMIN checklist was used to evaluate the quality of the studies. The quality of every measurement property was appraised by the update criteria of COSMIN. Evidence quality was judged using the modified GRADE approach. Results A total of 444 studies were retrieved in initial search. Six studies evaluating 4 tools were included in this study. All the included studies reported only content validity and reliability. The quality of evidence varied from very low to moderate. The quality of content validity and reliability of the included tools was sufficient except for the reliability of the maternal-fetal triage index. The obstetric triage acuity scale (OTAS) was found to have higher reliability than other tools. Conclusions Due to insufficient evidence, the conclusions about the quality of measurement properties of each obstetric triage tool may be uncertain. This review emphasizes the necessity for further studies with robust methodological quality on the measurement properties of obstetric triage tools.